SISA AKAR GIGI SEBAGAI FAKTOR RISIKO TERJADINYA HIPERTENSI PADA SUBJEK USIA LANJUT (Pendekatan Epidemiologik) - Janti Sudiono (Faculty of Dentistry, Universitas Indonesia, 2015)
It has been song suspected that there was an association between a focal infection with the prevalence of cardio-vascular disorders. The aim of this study was to observe the relationship betweem remaining infected teeth with epidemiological data of hypertension in elderly person. An epidemiology study was done on 184 elderly subjects (female 156, male 30) living in West and South of Jakarta Metropolitan City, Indonesia. Those subjects had been categorized as with and without hypertension (≥140/90 mmHg as 1999 WHO guidelines for hypertension) related to the none or with Mi score. There was 112 subjects with Mi score found in this study (PR=60.8%, CI 95% = 50.1% to 73.2%). Subjects with systolic and diastolic hypertension qA 111 (PR = 60.3%, CI 95% = 49.63% to 72.65%). The relative risk for hypertension (≥140/90 mmHg) with Mi as the risk factor was RR = 1.39 (CI 95% = 1.07 to 1.81). The Chi-square analysis showed that there was a significant association (p<0,05) between the remaining infected tooth (Mi score) and hypertension. The remaining infected tooth should be considered as one of risk factors to predict hypertension in elderly.